Faktor Penyebab Kecelakaan di Jalur Hijau Denpasar-Gilimanuk di Kecamatan Melaya, Kabupaten Jembrana - I Wayan Bagas Surya Adi Pratama; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
Accidents happen almost every time. Various factors are the cause of accidents, of course each region has its own factors but in general it can be influenced by various things like most cases. Various efforts were made, such as using special helmets for motorcycle riders, and using seat belts for car drivers, but there are still many traffic accidents until now. This study aims to analyze and describe the factors causing accidents on the Denpasar-Gilimanuk green line in Melaya District, Jembrana Regency. The number of vehicles that are so many today in Indonesia. In discussing this problem, the author uses an empirical legal research approach. Based on the results of the study, it can be seen that the factors causing accidents on the Denpasar-Gilimanuk green line in Melaya District, Jembrana Regency. Efforts to reduce the number of accidents by analyzing the data on the causes of accidents and also the various obstacles that are difficult to reduce the number of accident cases that occur by reviewing from various sources. Then efforts such as socializing about driving standards, obeying traffic regulations, repairing and adding facilities for safety and comfort for motorists.